2007
DOI: 10.4049/jimmunol.178.11.6912
|View full text |Cite
|
Sign up to set email alerts
|

Altered Innate Immune Functioning of Dendritic Cells in Elderly Humans: A Role of Phosphoinositide 3-Kinase-Signaling Pathway

Abstract: Aging represents a state of paradox where chronic inflammation is associated with declining immune responses. Dendritic cells (DCs) are the major APCs responsible for initiating an immune response. However, DC functions in aging have not been studied in detail. In this study, we have compared the innate immune functions of monocyte-derived myeloid DCs from elderly subjects with DCs from young individuals. We show that although phenotypically comparable, DCs from the aging are functionally different from DCs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
283
8
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(320 citation statements)
references
References 63 publications
27
283
8
2
Order By: Relevance
“…A phenomenon has been reported in children during the first decade of life that their pDCs numbers decline rapidly whereas the numbers of mDCs remain relatively stable (20,21). There are at least three studies demonstrated an age-related decline of pDC (22)(23)(24) but two other studies showed no changes (19,25). Conflicting findings have also been reported with regard to the age-related changes in mDCs.…”
Section: Discussionmentioning
confidence: 99%
“…A phenomenon has been reported in children during the first decade of life that their pDCs numbers decline rapidly whereas the numbers of mDCs remain relatively stable (20,21). There are at least three studies demonstrated an age-related decline of pDC (22)(23)(24) but two other studies showed no changes (19,25). Conflicting findings have also been reported with regard to the age-related changes in mDCs.…”
Section: Discussionmentioning
confidence: 99%
“…2 As humans age, immune responses become impaired, characterized by (1) reduced lymphopoiesis of new na€ ıve B and T cells, with novel BCRs 6 and TCRs, 7 respectively, (2) reduced dendritic cell (DC) function resulting in poor responses to inflammatory signals and lowered capacity to present antigen and to activate adaptive immune responses, 8 (3) poor germinal center formation, site of B cell expansion and selection, 9 and (4) decreased potential for T cell expansion, expression of activation markers, production of cytokines, diversity of TCR repertoire and delayed T cell responses to antigen. 7,10 Thus, these changes during aging help to explain the increased susceptibility to infection and reduced response to vaccinations in the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the alteration of the innate immune response to influenza infection is largely contributing to the pathogenesis of influenza virus besides the well-known role of the adaptive immune response [22]. DC appear to be altered not only in their basic functions such as phagocytosis, chemotaxis and production of IL-12, but also in their ability to activate naïve CD4+ T cells via antigen presentation [63,72] and this has been attributed to decreased PI3K activity [73]. Reduced PI3K was implicated in both age-related reduced DC migration and also as a negative regulator of TLR signalling.…”
Section: Dendritic Cell Functional Changes With Agingmentioning
confidence: 99%
“…• Chemotaxis decreased or no change [15,16,17] Free radical production decrease [15,16,17] Intracellular killing decreased [15,16,17] Rescue from apoptosis decreased [18] Intracellular signalling altered [14,19,20 Free radical production decrease [56] Intracellular killing decrease [56] Pro-inflammatory cytokine production increased [47,48,54,57] Intracellular signalling altered [29,47,48,49] Dendritic cells Phenotype no change or decrease [47,63,64] Subpopulations no change [63,64] Receptors number decrease or no change [29,65] Functions Phagocytosis decrease or no change [63,72,73] Antigen presentation decreased [63,72] Chemotaxis decreased [73] Intracellular killing decrease [63] Pro-inflammatory cytokine production increased [63,66,68] T cell priming altered [63,72] Cytokine production decreased or no change [84,88] T cell priming altered …”
Section: Innate Immunosenescence and Age-associated Pathologiesmentioning
confidence: 99%